Factors predictive of high disease activity early in the course of SLE in patients from a Latin-American cohort (2020)
To determine the factors predictive of disease activity early in the course of SLE (baseline visit). Patients from GLADEL, a multi-national, multi-ethnic, Latin-American lupus cohort were included. Disease activity was evaluated at baseline with the SLEDAI score. Demographic characteristics (age at diagnosis, gender, ethnicity, marital status, educational level, medical coverage and socioeconomic status) were assessed. Disease duration was defined as the time between the fourth ACR criterion and baseline. Time to criteria accrual was defined as the interval between the first and fourth ACR criterion. Use of glucocorticoids was recorded as the highest dose received before the baseline visit. Antimalarials and immunosuppressive drugs were recorded as use or not use. Univariable and multivariable analysis were performed. Model selection was based on backward elimination. One thousand two hundred sixty-eight patients were included; 1136 (89.6%) of them were female. Mean age at diagnosis was 29.2 (SD: 12.3) years. Five hundred sixty-five (44.6%) were Mestizo, 539 (42.5%) were Caucasians and 164 (12.9%) were African-Latin-Americans. The mean SLEDAI at baseline was 10.9 (SD: 8.4). Longer time between first and fourth ACR criterion, medical coverage, a dose of prednisone between 15 and 60mg/d, and the use of antimalarials were factors protective of disease activity, while Mestizo and African-Latin-American ethnicities were predictive factors. Mestizo and African-Latin-American ethnicities were predictive whereas antimalarial use, medical coverage, and longer time to criteria accrual were protective of higher disease activity early in the disease course.